Donor–Acceptor–Donor Structured Dyes with Balanced Photothermal Conversion Efficiency and Fluorescence Quantum Yield for Near-Infrared–II Mild-Temperature Photothermal Therapy - Xuan Sun; Zuyuan Zhang; Chunbai Xiang; Tianhe Qiao; Xin Wang; Gongcheng Ma; Dan Ding (Nano Biomedicine and Engineering)
Effective mild-temperature photothermal therapy (MTPTT) requires photothermal agents with high photothermal conversion efficiency (PCE) and balanced fluorescence quantum yield to enable efficient tumor treatment while minimizing damage to surrounding healthy tissues. In this study, we designed donor–acceptor–donor structured dyes, 4,4’-((6,7-di(thiophen-2-yl)-[1,2,5]thiadiazolo[3,4-g]quinoxaline-4,9-diyl)bis(thiophene-5,2-diyl))bis(N,N-bis(4-methoxyphenyl)aniline) (IT-STPA) and 4,4’-((6,7-di(furan-2-yl)-[1,2,5]thiadiazolo[3,4-g]quinoxaline-4,9-diyl)bis(thiophene-5,2-diyl))bis(N,N-bis(4-methoxyphenyl)aniline) (IT-OTPA), featuring furan-modified thiadiazolo-quinoxaline for near-infrared–II (NIR-II) fluorescence imaging and enhanced PCE. The furan and thiophene modifications promoted aggregation-induced emission, resulting in strong fluorescence emission (1 000–1 400 nm) while maintaining a high PCE of 48.5%. IT-OTPA was encapsulated into nanoparticles for improved aqueous dispersion and combined with the HSP70 inhibitor apoptozole (APZ) to form OTAPZ nanoparticles. The efficacy of this combination was evaluated both in vitro and in vivo, showing efficient tumor targeting and effective MTPTT under NIR laser irradiation. This study presents a promising approach for enhancing MTPTT through balanced photothermal and fluorescence properties, offering new possibilities for cancer treatment.